(untitled) (Innovative Technologica: Methodical Research Journal, 2023)
The article presents the results of research on melange yarn sampling in the RoCoS mechanical compact yarn spinning device of Rotorcraft. During the research, samples of yarn with linear density T=14.7 (Ne=40) tex and T=20 (Ne=30) tex were produced in the carding and combing spinning system. The physico-mechanical properties of the compact melange yarns obtained in the experiment were analyzed by comparing them with the properties of the spinning factory’s ordinary melange yarns. According to the results of the research, it was found that the melange yarn obtained in the RoCoS compact device is competitive in terms of its properties.